RANCANG BANGUN SISTEM LATIHAN SOAL DAN UJIAN TOEIC (TEST OF ENGLISH FOR INTERNATIONAL COMMUNICATION) BERBASIS WEB - Putro, Okma Winarko; Yunus, Mahmud (DINAMIKA DOTCOM, 2013)
TOEIC which stands for Test Of English for International Communication is one of the tests of proficiency in English that has been well-known and able to be an indicator of the participants skills in using English . In general, this test is divided into two parts , namely an understanding of testing hearing ( listening ) and reading ( reading ) where participants fill in their answers to the answer sheet of paper according to the questions that are heard on the sound and the written media.Formulation of the problem described in this research is how to build an online TOEIC exam application and web-based so as to optimize the test activities and learning through TOEIC exercises become more flexible , effective and efficient . The focus of the research is how to make the process of evaluation and assessment can be done optimally . In this case simplify performance management (administrators) to create questions , streamline time to correct answers and exam participants know the results in a rapid, precise and accurate . From the test results showed that application exercises and web -based TOEIC matter capable of processing data that has been inputted by administrators and present to the participants in accordance with the standards of performance in general . Test results can also be used to provide rapid assessment and analyze the results of the assessment scoring system.Suggestions can be submitted for the development and improvement of this web -based TOEIC test is to think about a better input mechanism to facilitate the user in the process of data input problem.Â Key words: TOEIC, online exam